The impact of soaking duration with phosphoric acid on the characteristics of halal gelatin obtained from New Zealand white rabbit bones (Oryctolagus cuniculus) - Samha, Hanifiya; Afifah, Ika Qurrotul (Journal of Halal Product and Research (JHPR), 2024)
The demands of Indonesia's numerous industrial sectors for gelatin still rely on imports. In general, gelatin produced using pork can cause serious problems for Hindus and Muslims. The product extracted from New Zealand White rabbit bones in this research has the potential to become halal gelatin. This research aimed to analyze the characteristic amide group absorption of gelatin in the Fourier Transform Infra-Red (FTIR) spectrum of the isolated gelatin from New Zealand White rabbit bones and to determine the effect of changing soaking time on the yield and gelatin characteristics. In the pre-treatment process, the sample was soaked using a 9% phosphoric acid solution for 48, 96, and 144 hours. The gelatin is then extracted at gradual temperatures for 12 hours. The characterization involved analyzing functional groups, water content, ash content, pH, and protein content. The typical absorption of gelatin functional groups in the form of amides A, I, II, and III was detected from FTIR spectrophotometric analysis. This study indicated that the soaking time significantly affected the yield, pH, ash content, and protein content of the gelatin produced, but did not significantly influencethe water content. The yield of gelatin from New Zealand White rabbit bones ranges from 4.08-6.56%. The water content of the gelatin is between 6.96-7.05%, and the pH value is 3.61-3.98. Both parameters meet the gelatin quality standards. However, the ash content of gelatin from New Zealand White rabbit bones, which ranges from 6.86-9.29%, does not meet the gelatin quality standards according to SNI 06-3735-1995 and GMIA 2012. The protein content of the rabbit bone gelatin, which is not regulated by the quality standards, ranges from 75.46-83.37%. The longer the soaking time, the higher the yield and protein content of the gelatin produced, and the lower the ash content. Keywords: Gelatin, New Zealand White Rabbit Bones, Soaking Time, Phosphoric Acid